KAJIAN PENYEBARAN ALIRAN POLUTAN SUNGAI CODE - , Doddy Meidiansyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Code River is one of the rivers passing through Yogyakarta city, which is located in a strategic area. The middle of river segments cross the densely populated urban areas, however some people considered the river to be an alternative place of waste disposal. This leads to degradation in the water quality of the Code River, therefore an analysis of pollutants flow distribution is needed. The research site is located along the Code River from the North Ringroad to South Ringroad, with approximately 10 km length. The method of analysis used is numerical simulation of pollutant transport, using one dimension model HEC-RAS software version 4.1. Simulation were run for the flow of February 14, 2012 and October 10, 2012 by entering the pollutant load concentration at segment points which are source of pollutants along the Code River. The parameters studied were BOD5 and DO. Based on the results of this research it can be concluded that the concentration values along the reach on February 14, 2012 the average BOD5 and DO respectively are in the range of 3,97 to 6,72 mg/l and 5,50 to 7,34 mg/l , while on the October 10, 2012 with a range of 6,80 to 16,07 mg/l and 9,41 to 34,94 mg/l. The largest sources of pollutants were originating from residential and tourism areas along the point RS 53-45 or the distance between 5,16 to 4,48 miles downstream, which were derived from thed drainage. The sewage comes from domestic, apartement, hotels and restaurants sewage. Most of DO concentration are eligible, because it exceeds the permissible minimum limit, while for BOD5 are not eligible because it exceeds the permissible maximum limit, therefore it can be concluded that pollution load from waste sorce site assessed have been polluting Code River. To get better results about Code River pollution, monitoring and evaluating the quality and quantity of waste sources at the monitoring points continuously based on time are required.